Rosa moschata ameliorates haloperidol-induced Parkinson's disease via reduction of neurodegeneration and oxidative stress - Badriyah S. Alotaibi; Uzma Saleem; Maryam Farrukh; Zunera Chaudhary; Nabia Anwar; Ifat Alsharif; Abdullah R. Alanzi; Tasahil S. Albishi; Fatima A. Jaber; Wedad Saeed Al-Qahtani; Muhammad Ajmal Shah (Asian Pacific Journal of Tropical Biomedicine)
Objective: To investigate the effect of Rosa moschata (R. moschata) extract on haloperidol-induced Parkinson’s disease (PD) in rats. Methods: Haloperidol (1 mg/kg) was given to rats intraperitoneally for 3 weeks for induction of PD. R. moschata extract (150, 300 and 600 mg/kg) was administered orally for 21 days. The neuroprotective role of R. moschata leaf extract in PD was explored by performing neurobehavioral tests and RT-PCR analysis and measuring neurotransmitters and oxidative stress biomarkers. Results: An improvement in motor functions and muscle strength was observed in PD rats treated with R. moschata extract. The levels of dopamine, serotonin, noradrenaline, superoxide dismutase, catalase, glutathione, and superoxide dismutase were significantly increased (P < 0.001), whereas acetylcholinesterase and malondialdehyde levels were markedly decreased by treatment with R. moschata extract (P < 0.001). The extract also markedly downregulated the mRNA expressions of IL-1β, α-synuclein, IL-1α, and TNF-α in brain tissue. Moreover, histopathological analysis indicated that neurofibrillary tangles and plaques were noticeably decreased in a dose-dependent manner in PD rats treated with R. moschata extract. Conclusions: R. moschata extract alleviates haloperidol-induced PD in rats by reducing oxidative stress and neurodegeneration. It may be used for management and treatment of PD. However, additional studies are required to confirm its efficacy and molecular mechanisms.